1999
DOI: 10.1515/jpm.1999.007
|View full text |Cite
|
Sign up to set email alerts
|

Treating previable twin-twin transfusion syndrome with fetoscopic laser surgery: Outcomes following the learning curve

Abstract: Fetoscopic laser occlusion of chorioangiopagous vessels within the vascular equator limits the duration of fetal pathophysiology in TTTS and results in neonatal outcomes superior to the modified procedure and other treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 17 publications
3
64
2
4
Order By: Relevance
“…In 1999, De Lia et al reported major impairment in 5% (5/93) of TTTS survivors after laser surgery at a mean age of 14 months (De Lia et al, 1999). No developmental Note: The first part of the Eurofetus trial is not included in this table because the children are more fully described in the follow-up of this trial.…”
Section: Long-term Neurodevelopmental Outcome In Ttts Treated With Lamentioning
confidence: 99%
“…In 1999, De Lia et al reported major impairment in 5% (5/93) of TTTS survivors after laser surgery at a mean age of 14 months (De Lia et al, 1999). No developmental Note: The first part of the Eurofetus trial is not included in this table because the children are more fully described in the follow-up of this trial.…”
Section: Long-term Neurodevelopmental Outcome In Ttts Treated With Lamentioning
confidence: 99%
“…A distribution plot of the laser time showed no evidence of a skewed pattern. The number of anastomoses ablated was not significantly different between the three groups [7 (5-12) in SAP vs 6 (5-11) in LAP and 8 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) in SPP, p = 0.47]. There were no significant differences seen between the three groups in terms of the amount of fluid either removed or infused during the case.…”
Section: Resultsmentioning
confidence: 84%
“…Recent results have shown better survival for laser therapy, and obliteration of chorionic plate anastomoses could halt the pathophysiological process. [11][12][13] Endoscopic laser ablation is feasible in pregnancies that are complicated by severe fetofetal transfusion syndrome and appears to be associated with improved perinatal outcome. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Resultados: a discordância média (SD) para DBP, CC, CA, CF e peso fetal um dia antes do laser foi 8,53% (5,28), 8,75% (2,76), 16,19% (4,85), 12,92% (5,13) e 28,50% (6,46). No segundo exame pós-laser os resultados foram 4,37% (3,55), 3,73% (2,71), 8,90% (4,42), 6,61% (4,99) e 19,11% (8,01); e a discordância do peso fetal ao nascimento foi 18,55% (8,74 interval between the ultrasound measurements was of at least two weeks.…”
Section: Objetivos: Avaliar Impacto Da Terapia a Laser No Crescimentounclassified